Analisis Pengaruh Rotasi Bumi terhadap Perbedaan Waktu dan Iklim Antar Wilayah - Arma Fuziah; Clarissa Oktoferin Sinaga; Mita Nasalisa Br Barus; Sri Andini; Widya Khairunisa; Elsa Kardiana (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
Understanding of the Earth's rotation is often limited to the alternation of day and night. However, its impact is far more complex, including the formation of time zones and varying climate patterns. The objectives of this study include analyzing the Earth's rotation's influence on the formation of time differences between regions based on longitude and the relationship between the Earth's rotation and climate variations caused by atmospheric movement and global wind patterns. This study employs literature review techniques using secondary data, which involves collecting data indirectly by studying the relevant objects. The use of secondary data related to Earth's rotational movement influences time and climate is based on findings from previous research. The findings of this study reveal that the Earth's rotation causes the alternation of day and night and time differences in each region, with each 15-degree difference in longitude resulting in a one-hour time difference. In terms of climate, the Earth's rotation produces the Coriolis force, which deflects the direction of wind and ocean currents, thereby forming atmospheric circulation patterns such as the Hadley, Ferrel, and polar cells. These circulation patterns determine temperature and precipitation distribution across various regions, so the Earth's rotation directly shapes the distinct global climate characteristics of each area